Zasloni za katodne elektronke - Županc Mežnar, Lea (Vakuumist, 1996)
Screen is the optical coating on the inner face plate of the cathode-ray tube, which converts the kinetic energy of the eleactron beam into the visible light. Screen includes the glass substrate and densely packed layer of the few microns large phosphor particles, coated by the aluminum film. In the article we will present the deposition methods of phosphor layer, the resolution and the light efficiency of the screen as well as the parameters which influence these two basic screen properties. We will also compare the conventional powder screens and newly developed thin film screens.
Keywords: elektronke; katodne elektronke; zasloni; elektrooptične lastnosti